2014
DOI: 10.1177/0969733014533233
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ professional values and attitudes toward collaboration with physicians

Abstract: The results of this study can be helpful to nurse administrators who are responsible for developing highly collaborative healthcare teams and for nurse educators who are focused on developing professional values in future nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 34 publications
9
69
0
2
Order By: Relevance
“…Our study finding that nurses with advanced education level had more positive attitudes compared to nurses with basic education was similar to a recent study on nurses from a tertiary hospital in the United States which also found that nurses with advanced education had better attitudes towards IPC (Brown et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study finding that nurses with advanced education level had more positive attitudes compared to nurses with basic education was similar to a recent study on nurses from a tertiary hospital in the United States which also found that nurses with advanced education had better attitudes towards IPC (Brown et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The JSAPNC questionnaire had been used by Hojat (Hojat et al, 2001(Hojat et al, , 2003 and various other authors (Brown, Lindell, Dolansky, & Garber, 2015;Delunas & Rouse, 2014;Onishi, Komi, & Kanda, 2013), and was found to correlate with study group differences (i.e. physicians, nurses, nursing, and medical students) in attitudes toward IPC and was useful to evaluate the effectiveness of programs developed to foster physician-nurse collaboration.…”
Section: Data Collectionmentioning
confidence: 99%
“…In some cultures, ''human dignity, safeguarding the client, caring, working together in a supportive'' are more important than other values; in some other cultures, values such as ''being honest, ambitious and responsible'' can have a higher priority. 8,[12][13][14]18,[25][26][27][28][29] For this Turkish sample, human dignity was reported to be the value highest in priority. This result suggests that nurses in Turkey value and respect humans and individuality the most in their clinical practice and that they place great importance on this value.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, lack of professional qualities negatively influences effective nursing services, the development of the profession and its image, and the quality of healthcare received by the public. [12][13][14] Nurses' professional values were created by the members of political and social systems, including professional nursing unions and educational institutions. These values are human dignity, autonomy, a sense of responsibility, security, and activism.…”
Section: Introductionmentioning
confidence: 99%
“…Advancing nursing knowledge and developing caring skills through continuous education would serve to enhance their professional values (Brown et al. ) and thus the quality of their care (Kim et al. ).…”
Section: Introductionmentioning
confidence: 99%